Prenatal feeding intentions versus postpartum feeding practices in HIV-exposed women on anti-retroviral therapy: A cohort study - Van De Venter, Claudine (Department of Public Health and Family Medicine, 2020)
Introduction The 2011 Tshwane declaration of support for breastfeeding in South Africa places strong emphasis on exclusive breastfeeding for HIV-exposed infants, overturning prior policy emphasising formula feeding. Prenatal feeding intentions of HIV-exposed women on antiretroviral therapy were compared to postpartum feeding practices. Factors associated to congruence of infant feeding intentions and subsequent practices were identified. Methods This prospective sub-study is nested within Phase 2 of the MCH-ART study. Five hundred and eighty-four women who consented to participate in Phase 2 (of a 3-phase study) were enrolled. Interviews took place at the Gugulethu Community Health Centre from July 2013 to December 2014 at late 3rd trimester and before seven days postpartum. Factors related with prenatal and postpartum characteristics were analysed to identify associations with congruence between infant feeding intentions and practices. Results The majority (81%) of the cohort had intended to exclusively breastfeed, 16% had intended to exclusively formula feed and 3% had intended to practice mixed feeding. By one week postpartum, 9% of women were exclusively breastfeeding, 2% were exclusively formula feeding and 90% were practicing mixed feeding. Congruence in the exclusive breastfeeding, formula and mixed feeding groups was 7%, 1% and 2% respectively. The risk of congruence in infant feeding intentions and practice was significantly less in women who disclosed their HIV-exposed status to anyone compared to those who chose not to disclose (aRR 0.56, 95% CI:0.37-0.93). Conclusions Although most women intended to exclusively breastfeed, the majority practiced mixed feeding and disclosure affected congruence. This indicates that the model used to advise women about infant feeding even in a study setting was not successful. When advising HIV-exposed expectant mothers, their disclosure status should be asked about and accounted for. The results indicate that despite previous study findings in similar socioeconomic environments, prenatal feeding intentions did not predict postpartum practice.